Saúde no Brasil: Algumas quest\~oes sobre o sistema único de saúde (SUS) - Sérgio Francisco Piola; Solon Magalh\~aes Vianna; Alexandre Marinho; Déa Carvalho; José Aparecido Ribeiro; Joelmir Rodrigues da Silva; Luciana Mendes Servo; Roberto Passos Nogueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This work is a compilation of studies produced at the Social Studies Department - Disoc/Ipea to support the elaboration of the document Brazil: the state of the Union - 2007. Health outcomes in the last decades, health policies after 1988 and the role of the government in health care are analyzed. Regarding this last topic, problems related to financing, sector regulation and services production by the Unified Health System are discussed. The study shows that, despite mprovements in several areas, there remain various issues, many of them related to management, to be addressed if the system is to be more effective and efficient in the provision of health care.
Keywords: H11; H51; H70; I10; I11; 330; Gesundheitswesen; Gesundheitspolitik; Brasilien